Caracterização epidemiológica de riquétsias (rickettsia spp.) em equinos e de seus potenciais vetores na região de Ji-Paraná, Rondônia - Fuverki, Renata Benício Neves (2024)
This study evaluated the infection caused by Rickettsia spp. in horses and ticks in the region of Ji-Paraná, Rondônia, in Western Amazonia, considered non-endemic for Brazilian Spotted Fever (BSF). A total of 400 horses were tested by Indirect Immunofluorescence Assay (IFA) for Rickettsia rickettsii, Rickettsia parkeri, Rickettsia amblyommatis and Rickettsia bellii. In addition, 1103 ticks collected from horses were morphologically identified following taxonomic keys. The overall seroprevalence of Rickettsia spp. was 21.75% (87/400), distributed in the rural, urban and peri-urban regions of the municipality, with emphasis on the latter. No positive samples were identified for R. rickettsii and R. parkeri. Of the total, 99.09% (1093/1103) of the equine ticks were identified as Dermacentor nitens, 0.54% (6/1103) as Rhipicephalus microplus, 0.27% (3/1103) as Amblyomma cajennense sensu stricto (s.s.) and 0.09% (1/1103) as Amblyomma sculptum, with ticks of the genus Amblyomma notably present in urban and peri-urban regions. This was the first study of rickettsiae seroprevalence in horses in the region of Ji-Paraná and, based on the results, there are indications of the circulation of R. bellii and R. amblyommatis (a species of the Spotted Fever Group – GFM) in these animals, considered sentinels for infection in humans. Considering that this is not an endemic area of BSF, the proportion of seroprevalence and of the vectors identified is considered low for the moment However, molecular studies of tick aliquots may provide better conclusions.